PENGARUH IKLIM KELAS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELASX DI SMA ADHYAKSA 1 KOTA JAMBI - Lestari, Febbe; Devina, Silvia; Saputri, Annisa Oktaviani (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of classroom climate on student learning outcomes in Economics subjects in class X at SMA Adhyaksa 1 Jambi City. The research method used in this research is a quantitative method with an explanatory survey design using simple linear regression analysis techniques. The results of the research show that there is a significant and positive influence of classroom climate on student learning outcomes in economics subjects in class X at Adhyaksa 1 High School, Jambi City. Thus, classroom characteristics or climate play a role and influence the quality of teaching so that it has implications for good learning outcomes.